Pemantapan Kemahiran Pembawa Acara Formal dan Nonformal bagi Guru di Kota Tangerang Selatan - Hartati, Rahma Dewi; Syafruddin; Ananda, Refisa; Maulina, Murni; Badriyah, Ratu; Yunus, Mohamad; Prakoso, Teguh (Universitas KH. Mukhtar Syafaat (UIMSYA), 2024)
The master of ceremony (MC) is one of the abilities that teachers must have when guiding activities carried out in schools, both formal and informal. However, the problem in the field is that not all teachers are ready if given the task of hosting even though they are used to teaching in class, due to the unpreparedness and inability of these teachers to host events with diverse audiences other than students. This community service activity aims to train teachers to prepare themselves to be flexible and communicative hosts. The method used is divided into preparation, implementation and evaluation focused on the preparation of emcee, namely the ability to compile event rundowns and make cue cards. The result of this activity is an increase in the ability to write a host guide in the form of a cue card containing important information that helps when doing emcee practice. In addition, there is flexibility and calmness of participants in guiding both formal and informal event activities